Fault-tolerant control design and evaluation for large-scale power networks - Qin, Lingzi (2015)
This paper studies the simulation of the devised distributed fault-tolerant control (DFTC) for large-scale electrical power system. The objective is to demonstrate the effectualness of the proposed algorithm which make the large-scale power network keep the expected system performance when the faults occur, meanwhile, detect and identify the faults coordinately. The paper focus on two kind of simulations by different block in Simulink/MATLAB. For the basic block simulation part, three-generator with infinite bus power system example is provided to illustrate the distributed fault-tolerant control (DFTC) controller with success. For the Power System Block (SimPowerSystem) simulation part, a steady power system and the typical faults in electrical power systems are the basis of the simulation. Future study should focus on solutions of problems in the Power System Block (SimPowerSystem) simulation.